Analisis Tindak Tutur Ilokusi dalam Kelas Daring tentang Studi Kasus pada Platform Ruangguru di Indonesia - Atria Windi Syarifah; I’anatul Khofifah; Farizka Aziza Ramadhani; Muhammad Fahda Mahasin; Ahmad Ma’arijul Amri; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Wulan Tri Puji Utami (STIKes Ibnu Sina Ajibarang, 2025)
Speech acts are communication activities that occur when someone delivers a speech to an interlocutor in a certain context and situation. Understanding the context and situation is very important to understand the intent of the speech. However, misunderstandings can occur, especially in indirect communication through digital media, such as YouTube channels. This study focuses on illocutionary speech acts that appear in 5 dare learning videos on the Ruangguru platform. Illocutionary speech acts contain the intent and function of speech, with various variations. The purpose of this study is to analyze the intent of speech in various illocutionary speech acts contained in the video. This study uses theoretical and methodological methods, with a qualitative descriptive approach. Data were collected by watching videos and recording illocutionary speech which was then analyzed. The results of the study showed five types of illocutionary speech acts: (1) assertive, (2) commissive, (3) directive, (4) expressive, and (5) declarative. These findings provide an understanding of the intent of the utterances spoken, so that the speaker's message can be understood well by the interlocutor.